Composite Resin's Resistant modified by silver for Compressive strength An In Vitro Study) ) (Journal of Hama University, 2019)
Introduction: Composite Resin is considered as an indispensable restorative material in the Dental Clinic. It has not anti antibacterial properties, so it creates suitable environment for germ-growth. It is modified by silver to acquire antibacterial properties.Aim of the research: This research aims to study the effect of adding silver to the Composite Resin on its compressive strength.Materials and methods: The study samples included (30) Composite- Resin (TGcore) cylinders with dimension of: ( height: 8 m.m and diameter: 4 m.m)  divided into three main groups according  to the ratio of silver addition (TopNano Tech Co. Taipei, Taiwan): ( 1'st group: 10 Composite- Resin cylinders free of silver, 2'nd group: 10 Composite- Resin cylinders modified by silver with the average of 0,5% by weight, 3'rd group: 10  Composite Resin modified by silver with the average of 1% by weight).The compressive strength was measured when samples were broken by using (TesT Device), made of Germany, from (Jung Instruments) company, Applys compressive forces according to the longitudinal axis of the sample.One-Way ANOVA and Bonferroni analysis was used.          Results: Statically results showed significant differences (p